1984
DOI: 10.1111/j.1528-1157.1984.tb04160.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Toxicity of Phenobarbital, Primidone, and Sodium Valproate in the Prevention of Febrile Convulsions, Controlled by Plasma Levels

Abstract: The effectiveness and toxicity of phenobarbital (PB), primidone (PRM), and sodium valproate (VPA), used exclusively in monotherapy, were compared in 95 children affected with febrile convulsions. Treatment was restricted to either complicated or simple febrile convulsions with risk factors. The effectiveness and toxicity of each drug were related to the daily dose and the steady-state plasma levels. PB (4.8 +/- 0.7 mg/kg/day) achieved plasma levels of 16.4 +/- 2.8 micrograms/ml and prevented febrile convulsion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 43 publications
(44 reference statements)
2
23
0
3
Order By: Relevance
“…[8] Other studies on use of Valproate in children. [79–12] have recoreded enuresis as side effect, the frequency being 1-7%. But surprisingly these studies are quite old and we could not find recent citations.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Other studies on use of Valproate in children. [79–12] have recoreded enuresis as side effect, the frequency being 1-7%. But surprisingly these studies are quite old and we could not find recent citations.…”
Section: Discussionmentioning
confidence: 99%
“…As with phenobarbital, adverse effects include behavioral disturbances, irritability, and sleep disturbances. 18 …”
Section: No Recommendationmentioning
confidence: 99%
“…[13][14][15][16] Primidone Primidone, in doses of 15 to 20 mg/kg per day, has also been shown to reduce the recurrence rate of febrile seizures. 17,18 It is of interest that the derived phenobarbital level in a Minigawa and Miura study 17 was below therapeutic (16 g/mL) in 29 of the 32 children, suggesting that primidone itself may be active in preventing seizure recurrence. As with phenobarbital, adverse effects include behavioral disturbances, irritability, and sleep disturbances.…”
Section: No Recommendationmentioning
confidence: 99%
“…Examining the literature reveals that in a study summarising the results of 16 trials and 1140 patients treated with different doses of valproate, side effects were observed in 26% of the patients, but discontinuation of the therapy was required in only 2% 7. Furthermore, in 48 children dosed with 30 mg/kg/day or more of sodium valproate for 22 months, a change in therapy was required in 5 patients (average dose=∼47 mg/kg/day) and withdrawal was required in 2 patients (average dose=∼43 mg/kg/day) 8. Similarly, in a study that followed up 118 patients for an average period of 18 months on valproate monotherapy with a mean dosage of ∼19.4 mg/kg/day, only four patients (3.4%) elected to discontinue treatment 9.…”
Section: Valproic Acid Side Effectsmentioning
confidence: 99%